The effects of forearm fatigue on baseball fastball pitching, with implications about elbow injury. Issue 12 (17th June 2016) - Wang, Lin-Hwa; Lo, Kuo-Cheng; Jou, I-Ming; Kuo, Li-Chieh; Tai, Ta-Wei; Su, Fong-Chin
ABSTRACT: This study investigated the contribution of flexor muscles to the forearm through fatigue; therefore, the differences in forearm mechanisms on the pitching motion in fastball were analysed. Fifteen baseball pitchers were included in this study. Ultrasonographical examination of participants' ulnar nerve in the cubital tunnel with the elbow extended and at 45°, 90° and 120° of flexion was carried. A three-dimensional motion analysis system with 14 reflective markers attached on participants was used for motion data collection. The electromyography system was applied over the flexor carpi ulnaris, flexor carpi radialis and extensor carpi radialis muscles of the dominant arm. Flexor carpi ulnaris muscle activity showed a significant difference during the acceleration phase, with a peak value during fastball post-fatigue ( P = 0.02). Significant differences in the distance between ulnar nerve and medial condyle on throwing arm and non-throwing arm were observed as the distance increased with the elbow movement from 0° to 120° of flexion ( P = 0.01). The significant increase of the flexor carpi ulnaris muscle activity might be responsible for maintaining the stability of the wrist joint. The increased diameter might compress the ulnar nerve and cause several pathological changes. Therefore, fatigue in baseball pitchers still poses a threat to the ulnar nerve because the flexor carpi ulnaris and flexor carpi radialis all originate from the medial side of the elbow, and the swelling tendons after fatigue might be a key point.